2007
DOI: 10.1007/s00192-007-0389-6
|View full text |Cite
|
Sign up to set email alerts
|

Prospective results after first-time surgery for obstetric fistulas in East African women

Abstract: The objective of this study was to document the complications, outcomes and causes of obstetric fistulas in East African women who underwent first-time surgical repair. Attention was also paid to social background and characteristics of the patients. Data were collected prospectively from patients operated on in the period from January 2001 to August 2003. Only patients who received first-time surgery and whose fistula had been caused by obstructed labour were included in the study. Eight hundred eighty-eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
64
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 15 publications
11
64
2
1
Order By: Relevance
“…This rate varies between 2.2% and 4% according to authors throughout the world [5] [7] [11]. The average age at the time of surgery is 35 years (16 -76 years) in our series.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This rate varies between 2.2% and 4% according to authors throughout the world [5] [7] [11]. The average age at the time of surgery is 35 years (16 -76 years) in our series.…”
Section: Discussionmentioning
confidence: 71%
“…This age depends on the availability of surgeons in the area. The average age at onset of fistula was 25 years and the average length of time our patients had fistula was 8 years (4 months to 61 years) due to lack of availability of surgeons, 2 to 4 years for most authors around the world [5] [7] [9] [16] except Tegbeu who found 8.5 years in Cameroon. The duration of the index delivery labor that resulted in the formation of the obstetric fistula was 3 days as most authors have also noted in their series [9] [16] [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, there is a shortage of reliable data around social, demographic and clinical factors associated with time to recovery from obstetric Fistula surgical repair that will be valuable for managing health care institution through planning, monitoring and evaluation of quality of care as well as use of human and material resources [29][30][31][32][33][34][35].…”
Section: Significance Of the Studymentioning
confidence: 99%
“…40,41 However, in the developing countries, obstetric fistulae are common. 42 Estimates indicate that 2-3 millions women live with obstetric fistulae worldwide, the majority of whom are in Africa and Asia. [43][44][45] Fistulas are preventable and treatable, however, many women are still unaware of the availability of treatment and 80% of them never seek treatment due to lack of knowledge.…”
Section: Fistulae In the Developing Worldmentioning
confidence: 99%